Development of english lyrical poetry - Cress, Alverta May (My University, 1894)
Introduction: The English lyrics as one author defines them are short poems, “dealing with one thought, essentially melodious in rhyme and structure, and if a metaphor may be taken from a sister art, a simple air without progression, variation, or accompaniment.” We are accustomed to hear them spoken of as songs, at the present day—a term rightly applied, since these poems are written to be set to music. There is no form of literature that is so universally enjoyed by the people as the lyric. As far back as history traces the English people one may find this same love of song so characteristic of our race today. We know the early ancestors were in possession of a great many of them although we have only a few in the ancient books—the Exeter and Vercelli—and also several old manuscripts. The early literature like the people was very rude. In Beowulf we find this curious poem translated by Thorp. It seems as strange and wild in spirit as the people of those days.
Citation: Cress, Alverta May. Development of english lyrical poetry. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: English; Poetry; Lyric; Literature; Beowulf; Theses; Manuscripts (documents)